Loading rate and mineralogical controls on tensile strength of rocks: a machine learning view - Tie, Jiahao (2023)
Machine learning models show the effects of loading rate and mineralogical composition on rock tensile strength. Difference between the indirect and direct tensile strengths becomes larger with a higher loading rate. Training with dissimilar mineralogical compositions reduces prediction reliability of machine learning models.